Using English Movies to Improve the Listening Ability to the Students of SMPN 1 Maiwa - Hermansyah, Sam; Hasan, Hasan (Majesty Journal, 2021)
This research aimed to improve the listening ability of the students of SMPN 1 Maiwa by using English Movies. The problem statements were: 1). to what extent may the students improve their listening ability through using English Movies? 2). to what extent is the students’ attitude toward the application of using English Movies? The objectives of the research were to find out whether or not English Movies can improve the students’ listening ability and to find out the students’ attitude toward the application of using English Movies in improving their listening ability. The researcher applied pre-experimental method. The population of the research was the students of SMPN 1 Maiwa in academic Year 2018/2019 which consists of 20 students. Ten students from the first class and ten students from the second class. The writer used random sampling in taking the sample. The researcher used tests and questionnaire to collect data. The researcher distributed listening test through pretest and posttest and she distributed questionnaire to collect information about their attitude toward the application of using English Movies. The result of the research showed that the students’ listening ability had poor score in pretest. After treatment, their listening ability is significantly increased. It can be seen from their score that changed became good. The data analyzed using t-test showed that the value of t-test is higher than t-table (7.98>2.093). It can be concluded that English Movies is effective in improving the students’ listening ability. Data from questionnaire showed that students have positive attitude toward the application of using English Movies.